Validation of a stability-indicating spectrometric method for the determination of sulfacetamide sodium in pure form and ophthalmic preparations - Sofia Ahmed; Noureen Anwar; Muhammad Ali Sheraz; Iqbal Ahmad (Wolters Kluwer Medknow Publications, 2017)
Introduction: Sulfacetamide sodium is a widely used sulfonamide for ophthalmic infections. Objective: A number of analytical methods have been reported for the analysis of sulfacetamide but they lack the ability to determine both the active drug and its major degradation product, sulfanilamide, simultaneously in a sample. Materials and Methods: In the present study a simple, rapid and economical stability-indicating UV spectrometric method has been validated for the simultaneous assay of sulfacetamide sodium and sulfanilamide in pure form and in ophthalmic preparations. Results: The method has been found to be accurate (recovery 100.03 ±0.589%) and precise (RSD 0.587%) with detectable and quantifiable limits of 1.67×10-6 M (0.04 mg%) and 5.07×10-6 M (0.13 mg%), respectively for the assay of pure sulfacetamide sodium. The method is also found to be accurate and precise to small changes in wavelength, pH and buffer concentration as well as to forced degradation. The study further includes the validation of the method for the assay of pure sulfanilamide in solution, which has been found to be accurate, precise and robust. Conclusion: The results indicate that the proposed two-component spectrometric method is stability-indicating and can be used for the simultaneous assay of both sulfacetamide sodium and sulfanilamide in synthetic mixtures and degraded solutions.